The Straits of Malacca and Singapore: Maritime Conduits of Global Importance - Mohd Hazmi Mohd Rusli; Ade Maman Suherman; Aryuni Yuliantiningsih; Wismaningsih Wismaningsih; Noer Indriati (Sciedu Press, 2024)
Indexed by ERA